'Tis the season (Raton Range Raton, NM, 1989)
Article is about the Christmas performance and the lighting of the City of Bethlehem.
Newspaper article + two photographs 1) Raton Catholic School Students and 2) Homer Hill
Master list item #: 7
File location is in the Raton file Cabinet
Keywords: Hill, Homer -- Lions Club International Director; Raton Catholic School; Lions Club; Christmas Plays; Christmas Lighting; Holiday Displays; Christmas Spirit; Annual Traditions; City of Bethlehem; Climax Canyon; Raton, New Mexico